The nexus of women and ‘Clan Crime’: unravelling the dynamics and constraints - Jaraba, Mahmoud (Trends in Organized Crime, 2024)
Despite its prominence in public debate, scholars have given little attention to women’s roles in ‘clan crime’ in Germany. This article aims to bridge this gap through in-depth ethnographic fieldwork and 18 interviews conducted with women from various ‘clans’ throughout the country. These women are part of the al-Rashidiyya community with origins in Mardin, Turkey. Adopting an anthropological perspective, I seek to uncover the underlying historical, cultural, social, and contextual factors shaping women’s participation in ‘clan crime’, whether through indirect support or direct involvement. My findings reveal that women play a crucial, albeit often hidden, role in ‘clan’ dynamics and criminal activities, which frequently go unrecorded by the police. Although they are unlikely to hold leadership positions, women exert their influence through other means, such as shaping their children’s behavior, actively encouraging their sons to engage in criminal activities, or transmitting criminal norms and roles through socialization. Women themselves may also engage in crimes such as money laundering and financial fraud. By shedding light on these dynamics and emphasizing the importance of gender dynamics in the broader study of criminal groups, I expand our understanding of organized crime and similar clan-like mafia structures.